Prostitution Legislation Reforms in Western Australia: What Indonesia Can Learn - Komang Ayu Kartika Sari (Universitas Udayana, 2014)
The proposed approach in prostitution in WA needs to be redirected to decriminalisation system with the implementation of harm reduction to achieve the effective public health efforts. Intensive health promotion efforts, including accurate information for HIV positive sex workers and health policies to reduce stigma and discrimination for all sex workers are needed to provide supportive environment for sex workers, which will enable their health and safety issues to be addressed. These approaches should be applied in the Indonesian context as well, where sex workers are still illegal and mostly criminalised. Decriminalisation system is needed even when there is no idea of legalising prostitution yet in Indonesia. In addition, as brothel-based sex workers are more organised and easier to reach, they have higher potential to participate in the health promotion efforts. The established brothels in Indonesia therefore should be well managed in terms of health and safety in the premises, without any human rights violation and criminalisation.